Examining the influence of human resources practices on turnover intention: A study among hotel employees - Komathy, Santhirasaygaran (2013)
While performing their duties in an organization, an employee tied up to a human resource practices which consists of internal career opportunity, training, result oriented appraisals, Employment security, participation and job description to retain in an organization. This research title is aimed to determine the influences of internal career opportunity, training, result oriented appraisals, employment security, participation and job description on turnover intention. The objective of this study is; to understand the influence of the selected human resource practices on turnover intention. A total of 169 questionnaires were distributed to one of the selected Telecommunication Company. Data were analyzed using both descriptive and inferential statistical analysis to interpret data. Research findings revealed there was turnover intentions exist among the respondents. Significant values for each element in independent variable which the item of reward such as result oriented appraisal, training, and participation. The higher significant value of independent variables are result oriented appraisal and item benefits, 0.538> 0.05